The Working Environment as a Catalyst for Organizational Efficiency - De Diego-Vallejo, Raúl (2015)
In recent years, it has been done a several amount of studies about working environment. Working environment is, by definition, a set of perceptions shared by workers from the same workplace. This research is focused on studying the relationship between the working environment and different variables of educative organizations. The sample is constituted by 649 educational workers with an average age of 51.9 years old and a standard deviation of 6.28. The results revealed that, working environment in team-works is influenced by the social support perceived by workers.